Sollers point [videorecording (DVD)] - Porterfield, Matt; Lombardi, McCaul; Belushi, James, 1954-; Guiry, Thomas, 1981- (Oscilloscope Laboratories, 2018)
A small time drug dealer under house arrest at the home of his father, re-enters a community scarred by unemployment, neglect and deeply entrenched segregation. There, he pushes back against his surrounding limitations as he tries to find a way out of his own internal prison.